Combining traffic simulation with bayesian networks for improved quantification of accident risk index - Michail, Harris; Mouskos, Kyriacos C.; Gregoriades, Andreas (My University, 2012)
Traffic phenomena are characterized by complexity and uncertainty, hence require sophisticated information management to identify patterns relevant to safety and reliability. Traffic simulation methods have emerged with the aim to evaluate traffic congestion and improve road safety. However, assessment of traffic safety and congestion requires significant amount of data which in most cases is not available. This work illustrates an approach that aims to alleviate this problem through the integration of two mature technologies namely, simulation-based Dynamic Traffic Assignment (DTA) and Bayesian Belief Networks (BN). The former generates traffic flow data, utilised by a BN model that quantifies accident risk. Traffic flow data is used to assess the accident risk index per road section and hence, escape from the limitation of traditional approaches that use only accident frequencies to quantify accident risk. The development of the BN model combines historical accident records obtained from the Cyprus police and data generated from the DTA simulation.
Keywords: Traffic safety; Traffic flow; Information management; Computer simulation; Accidents--Prevention